Finite modeling of SAW resonator for DF-1 cells - Jamil, Nadira; Nordin, Anis Nurashikin; Voiculescu, Ioana (2010)
In this work, a finite element modeling of surface acoustic wave biosensors is presented. These resonators are formed using a lithium niobate substrate with Al electrodes as the interdigitated transducers. A study has been made to compare the efficiency and sensitivity of the acoustic wave biosensors in analyzing the DF-1 cells. DF-1 animal cell were modeled as a load on the acoustic wave sensors. In order to achieve the objectives, COMSOL Multiphysics #x2122; was the primary software to perform the simulations. Multiple designs of SAW resonators are performed, varying in lambda, type of ports and the presence of delay line. These models were simulated to determine their resonant frequency as well as frequency shift due to the loading of a substance which is the DF-1 cells. This paper presents the biosensor prototype utilizing acoustic wave biosensors with and without delay lines; and compares their performance in the detection of DF-1 cells.